PROGRAM PELATIHAN MOTORIK KASAR UNTUK ANAK CEREBRAL PALSY TIPE SPASTIK BERBASIS KELUARGA - Ina Herlina Apriani, - (2020)
Cerebral Palsy (CP) is a non-progressive disorder or damage to the brain that occurs in the process of growth and development, especially in motor development. The family must be able to provide training or gross motor stimulation to children. The purpose of this study is to develop a gross motor training program for children with spastic cerebral palsy by empowering parents. In the preparation of the program using a qualitative approach with descriptive research methods, and to determine the success of the program the method used was experiment. The subject of the study was a child with the initials RMI who had a Spastic type of Cerebral Palsy and a family in the house who interacted with the child daily. Observation, tests, interviews and documentation were used to explore data related to the objective conditions of gross motor skills, to find out the family's ability to train motor skills to children, to compile programs and to see the impact of program implementation. The results of the data analysis show that the initial conditions for gross motor skills of children who are still unable to crawl such as the movement patterns of lizards and families who do not know how to properly practice creeping activities, however, after the program is implemented by the family, it has an impact in the form of increasing children's creeping skills, in addition, it strengthens them. arm muscle; the limbs and neck muscles of the child. The gross motor skills training program for children with family-based Spastic Cerebral Palsy contains four aspects, namely: General Massage, Joint Mobilization, Patterning Therapy, and Bobath Exercise. Adherence of the program to the needs of children and paying attention to family conditions will lead to optimal gross motor skills of children.